Uso pedagógico de software de simulação para auxiliar o desenvolvimento da aprendizagem significativa de conteúdos de eletroquímica no ensino médio - Gomes, Alexandre D' Emery da Silva (2017)
An important strategy to favor a student's chemistry learning, is characterized by a conception of alternative practices, attached to the use of pedagogic educational software, highlighting the use of computer simulation, which, if methodologically based, may favor, together with students, a construction of scientific knowledge and the appropriation of new knowledge and skills. In this context, the present dissertation aims to offer contributions, to conceive a pedagogical practice of teaching and collaborative learning, incorporating the use of computer simulation on Electrochemistry’s issues. Therefore, it promoted a discussion of the phenomenological dynamics, associated to electrochemical cells, galvanic and electrolytic types. Such actions, may eventually replace or be pedagogically articulated in practices performed on laboratory workbenches. In the theoretic, methodologic and practical assumptions adopted, stand out: Ausubel (Meaningful Learning), Valente and Almeida (the pedagogical use of the computer) and Ribeiro and Almeida (Integration of ICTs and scientific practices to facilitate the learning’s development). Methodologically, it was adopted a quality research approach, with a research-action character. A field research, composed by three steps or stages, was performed by a research-educator, together with high school’s students of a Public School in Horizonte, Ceará, with its field data collected from school pupils, through three questionnaires’ evaluation. In the first stage, by the questionnaire I, the school pupils’ profiles were mapped and how they notice the possibilities of ICT’s use in the school and residentially. In a second stage of field research, was applied to questionnaire II, to map students' perceptions, regarding to the teaching of chemistry and their pre-existing knowledge of electrochemistry. Sequentially, theoretical lectures were given to help and facilitate the process of building new knowledge and/or re-signification of previous electrochemistry knowledge. Also in the second stage, a practice was carried out with the students, involving the development of learning situations and problems of electrochemistry, over the pedagogical use of computer simulation. Therefore, two PhET simulators were used to promote the study of electrochemical cells: the Daniel pile and electrolysis. Collaboratively and interactively, the students were able to experience moments of: evaluation of the phenomenological dynamics, analysis, discussion and (re) signification, involving previous concepts and an acquisition of new knowledge. Complementarily, in the third stage, the questionnaire III was applied, for changes of students’ points of view. The analyzed results revealed preliminary evidences of physical and facilitation events, followed during a pedagogical appropriation of the simulators’ use and their eventual integration with the development of learning process, which contributed to the pedagogical vision change of the school pupils and the Researcher-educator.